Dinâmica demográfica e políticas públicas : influências no regime de previdência social - Menezes, Igor da Cruz (2016)
The General Social Security Regime in Brazil operates guided the contributory character, in simple lines, we can say that the economically active population, also called taxpayers, is responsible for the contribution to the payment of pensions of beneficiaries or retired. Given the evidence of the subject that guides the difficulties of this regime to shoulder their responsibilities today, this work aims braiding age transition that took place in Brazil in the last decade, relating it to the social security dependency caused by this phenomenon, as well as the impacts imposed by these demographic changes in the General Social Security system (RGPS), and appreciate what measures have been taken regarding the challenges of establishing the sustainability and survival of this system